THE EFFECT OF LOW-FIBER DIETS ON COLORECTAL CANCER INCIDENCE IN SOUTHEAST AND EAST ASIA: SYSTEMATIC REVIEW AND META-ANALYSIS - Tia Eka Novianti; Qonita Rachmah; Merryana Adriani (Universitas Airlangga, 2023)
Introduction : Colorectal cancer is a malignant tumor that grows in the colon tissue. In the Asian region, in 2018, cases and deaths from colorectal cancer are highest in East Asia (there were 736,573 cases and 325,128 of them died) and Southeast Asia (there were 95,223 cases and 52,475 of them died). Aims: Several studies have been conducted regarding the effect of a low-fiber diet and an increased risk of colorectal cancer, but it still shows mixed results. Methods: This study is an unobstrutive study with a systematic review and meta-analysis method. Data sources came from 14 primary studies with a case-control study design that met the inclusion criteria. Data analysis was performed using CMA software trial version 3.0 with a confidence level of α = 5%. Research with low-fiber diet variables shows heterogeneous variations in results so that the chosen model is random effect model. Result: The analysis states that there was a significant relationship between a low-fiber diet (CI: 0.421–0.867) and an increased risk of colorectal cancer due to the role of soluble and insoluble fiber. Lack of intake of soluble fiber can decrease insulin action and blood sugar control or the production of short-chain fatty acids, whereas insufficient intake of insoluble fiber can increase the potential for interactions between mutagens and colonic mucosa. Conclusion: The results of the study are expected to be an input for a proper diet so that there is no increase in cases of colorectal cancer.